Stable properties under weakly geometrically flat maps - Barlet, Daniel; Magnússon, Jón (MATHEMATICA SCANDINAVICA, 2025)
In this note we show that a weakly geometrically flat map π M→ N between pure dimensional complex spaces has the local lifting property for cycles. From this result we also deduce that, under these hypotheses, several properties of M are transferred to N.